Awareness of postural orthostatic tachycardia syndrome is required in adolescent syncope. Issue 45 (11th November 2022) - Kim, Dong Hyun; Park, Ji Young; Kim, Su Yeong; Lee, Na Mi; Yi, Dae Yong; Yun, Sin Weon; Lim, In Seok; Chae, Soo Ahn
Abstract : We investigated head-up tilt test (HUTT) results across age-groups in syncope/presyncope patients to establish pediatric postural orthostatic tachycardia syndrome (POTS) characteristics. We retrospectively reviewed syncope patients' medical records. Adolescents were defined as 10 to 19 years old, adults as 20 to 59 years old, and older individuals as ≥60 years old. From HUTT results, we determined POTS prevalence and differences among the age-groups. We included 147 adolescents, 269 adults, and 123 older patients. Seventy (13.0%) patients (61.4% females; median age: 20 [17–25] years) were diagnosed with POTS. The syndrome was more prevalent among adolescents (33 [22.4%]) than adults (37 [13.8%]), and was absent among older individuals. Affected adolescents had significantly lower resting diastolic blood pressure (DBP) and heart rate (HR), and converted to maximum HR more rapidly than adolescents without the syndrome during the passive phase. Adolescents with POTS demonstrated several unique characteristics compared to adults with and adolescents without this syndrome. POTS may be underrecognized among syncope and presyncope patients, among which 22.4% of adolescents were diagnosed with the syndrome. POTS should be considered when evaluating syncope patients.